2020
DOI: 10.1186/s13059-020-02099-9
|View full text |Cite
|
Sign up to set email alerts
|

Contiguous and stochastic CHH methylation patterns of plant DRM2 and CMT2 revealed by single-read methylome analysis

Abstract: Cytosine methylome data is commonly generated through next-generation sequencing, with analyses averaging methylation states of individual reads. We propose an alternative method of analysing single-read methylome data. Using this method, we identify patterns relating to the mechanism of two plant non-CG-methylating enzymes, CMT2 and DRM2. CMT2-methylated regions show higher stochasticity, while DRM2-methylated regions have higher variation among cells. Based on these patterns, we develop a classifier that pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 61 publications
(104 reference statements)
1
19
0
Order By: Relevance
“…As said earlier, while vertebrate DNA cytosine methylation is primarily found in the CG context, plants have significant levels of DNA methylation in the CG, CHG and CHH contexts [39, 15]. To focus on CHG and CHH methylation we selected five plant species for which BS-Seq data was available, namely (1) Arabidopsis thaliana representing the Brassicales order, (2) rice ( Oryza sativa ) representing the Paoles order (the only monocotyledons in our study), (3) tomato ( Solanum lycopersicum ) representing the Solanales order, (4) cucumber ( Cucumis sativus ) representing the Cucurbitales order, and (5) cowpea ( Vigna unguiculata ) representing the Fabales order.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As said earlier, while vertebrate DNA cytosine methylation is primarily found in the CG context, plants have significant levels of DNA methylation in the CG, CHG and CHH contexts [39, 15]. To focus on CHG and CHH methylation we selected five plant species for which BS-Seq data was available, namely (1) Arabidopsis thaliana representing the Brassicales order, (2) rice ( Oryza sativa ) representing the Paoles order (the only monocotyledons in our study), (3) tomato ( Solanum lycopersicum ) representing the Solanales order, (4) cucumber ( Cucumis sativus ) representing the Cucurbitales order, and (5) cowpea ( Vigna unguiculata ) representing the Fabales order.…”
Section: Resultsmentioning
confidence: 99%
“…In plants and other non-vertebrates, cytosine methylation in the CHH and CHG contexts (where H represents any base except G) is almost as common as methylation in CG context [13, 14]. It is now well-understood that distinct molecular mechanisms in the cells regulate cytosine methylation and demethylation depending on the context [15, 16, 17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Future work is needed to investigate the presence and potential role of CHH islands in almond and their possible functions and impact on NBF potential. CHH methylation is biologically intriguing given that it is independent of demethylase activity and chromatin structure; therefore, its characterization may require additional tools to better understand its dynamics ( Harris and Zemach, 2020 ). Additionally, CHH methylation has been shown to be involved in regulating the expression of transposable elements in plant genomes ( Harris and Zemach, 2020 ; Wang and Baulcombe, 2020 ; Xin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…CHH methylation is biologically intriguing given that it is independent of demethylase activity and chromatin structure; therefore, its characterization may require additional tools to better understand its dynamics ( Harris and Zemach, 2020 ). Additionally, CHH methylation has been shown to be involved in regulating the expression of transposable elements in plant genomes ( Harris and Zemach, 2020 ; Wang and Baulcombe, 2020 ; Xin et al, 2021 ). Prediction analysis using gene expression data in this study indicates expression of transposable element 1 from both almond and peach are highly predictive of NBF exhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a genome-wide decrease in CHH methylation was previously associated with hybrid vigour in Arabidopsis , and correlates with a general decrease of 24 nt siRNAs 29 , 32 . Nonetheless, plant DNA methylation in CHH context is considered to be highly stochastic 33 , and it is, therefore, remarkable to observe that DMRs have been found almost exclusively hypomethylated. However, previous studies performed on epigenetic hybrids showed that only a subset of DMRs can be directly associated with heterosis 31 , and we also found only little overlap among differentially express genes and DMRs in hetero-grafted vigorous scions.…”
Section: Discussionmentioning
confidence: 99%